ORGANIZATION OF PARTICIPATORY BUDGET (PB) DEVELOPMENT IN LATVIAN MUNICIPALITIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In recent years, negative trends have been observed in Latvia in connection with society's reluctance to get involved in political processes and, therefore, also in state and local government administration. The number of voters who voted in the 2017 local government elections in the amount of 50.39% was assessed as an alarming indicator. In the municipal elections of 2021, when only 34.01% of eligible voters voted, the result causes alarm. The results of the elections and studies show that there is alienation of the population from the government and the current trust in the state administration is very low. Citizens do not believe that they can influence the development and management processes of the state and local governments. One of the reasons for distrust is the lack of feedback from the municipality or the inability or unwillingness of the municipality to solve the problems raised by the residents. The need to ensure public participation is defined in several regulatory acts of the Republic of Latvia. Residents' involvement is a long-term process, in which the prerequisite is the building of trust between the municipality and the residents. If citizens have the opportunity to determine how a part of the municipal budget will be spent, municipalities will promote democratic values and the opportunity to participate in the decision-making process. Participatory budget in local governments is one of the ways to try to bring citizens closer to local government. By 2025 in Latvia, it must be included in the municipal budget.The aim of the work is to find out the readiness of Latvian local governments to plan a participation budget in 2025 in the amount specified in the Law on Local Governments.The tasks of the work are to study the findings of various authors on public participation and the participatory budget, to analyse the normative documents on the participatory budget adopted in Latvia and to conduct a situational study of the experience of local governments and their readiness to implement a participatory budget by 2025. Methods used in the work - monographic method, analysis of various theoretical sources, regulatory acts, sociological research method - interview, - for finding out the opinion of experts and logically constructive method - for forming judgments and recommendations.